Recent Advances in Low Valent Thorium and Uranium Chemistry - Tsoureas, Nikolaos; Vagiakos, Ioannis (Inorganics, 2024)
The synthesis, isolation, and characterisation of well-defined low-valent actinide complexes are reviewed with a main focus on compounds featuring uranium and thorium metal centres in formal oxidation states ≤ +3. The importance of the ligand environment in enabling access to these highly reactive species, as well as its influence on ground state electronic configurations and their reactivity, are emphasised. Furthermore, we highlight cyclic voltammetry (C.V.) studies as a more widely used method that can guide the synthesis of these highly reducing species.
Keywords: actinide; low valent; organometallic; small molecule activation; thorium; Uranium